Taxonomi Informasi Produksi pada Industri Manufaktur dalam Industri 4.0 - Kusumawati, Tri Ika Jaya (Jurnal Buana Informatika, 2018)
Abstract. Digitalization in the manufacturing industry to date continues to grow. Various technologies that support its success are built and continue to be researched to create openness. Data disclosure is a research topic that has not been resolved because it refers to the large data circulating on the internet. In industry 4.0 production machinery, production needs and some elements of production support communicate efficiently with data connected via the internet. To absorb and classify data, the filtering and sorting stages of the word are needed. Taxonomy is a technique in mapping the relationship of words and meanings of words which are the data themselves. In this study a taxonomy of production activity was designed in the manufacturing industry engaged in textile. The number of terms in the textile industry and the results of textile production, it is necessary to make a tax taxonomy in the order of interconnected meanings. This study refers to research to create an ontology-based database in the current supply chain management. The results of this study are mapping models in the form of taxonomies that are made using the method of methontology. Methontology is the development of ontologies that propose expressions of ideas as a set of intermediate representations (IR) and produce ontologies using translators. In this method there are five stages: Specifications, Conceptualization, Formalization, Implementation and Maintenance. Testing the success of taxonomies used OntoQA which is a matrix for calculating the strength of attachment between classes. This research continues to be refined by developing it in the subsequent research titles. Keywords: Industry 4.0; manufacturing industry; textile; taxonomy; methontology.Abstrak. Digitalisasi dalam industri manufaktur sampai dengan saat ini terus berkembang. Berbagai teknologi yang mendukung keberhasilannya dibangun dan terus diteliti agar tercipta keterbukaan. Keterbukaan data merupakan topik penelitian yang belum terselesaiakan karena mengacu kepada data yang besar yang beredar di internet. Dalam industri 4.0 mesin produksi, kebutuhan produksi serta beberapa element pendukung produksi berkomunikasi secara efisien dengan terhubungnya data melalui internet. Untuk menyerap dan mengklasifikasikan data dibutuhkan tahap penyaringan dan pemilahan makna dari kata. Taxonomi merupkan salah satu teknik dalam memetakan keterkaitan kata serta makna dari kata yang merupakan data itu sendiri. Pada penelitian ini dirancang sebuah taxonomi kegitan produksi pada industri manufaktur yang bergerak dibidang textile. Banyaknya istilah dalam industri textile dan hasil dari produksi textile, maka perlu dibuatkannya sebuah taxonomi data dalam susunana makna yang saling berhubungan. Penelitian ini mengacu kepada penelitian untuk membuat database berbasis ontologi dalam arus supply chain management. Hasil dari penelitian ini adalah model pemetaan dalam bentuk taxonomi yang dibuat menggunakan metode methontology. Methontology adalah pengembangan ontologi yang mengusulkan ekspresi ide sebagai seperangkat representasi menengah (IR) dan menghasilkan ontologi menggunakan penerjemah. Dalam metode ini ada lima tahap: Spesifikasi, konseptualisasi, Formalisasi, Implementasi, dan Pemeliharaan. Pengujian keberhasilan taxonomi menggunakan OntoQA yang merupakan matriks perhitungan kekuatan keterikatan antar class. Penelitian ini masih terus dalam penyempurnaan dengan dikembangkannya dalam judul-judul penelitian berikutnya. Kata Kunci: Industri 4.0; industri manufaktur; textile; taxonomi; methontology.